Analytical demands to use whole-genome sequencing in precision oncology. (September 2022) - Meggendorfer, Manja; Jobanputra, Vaidehi; Wrzeszczynski, Kazimierz O.; Roepman, Paul; de Bruijn, Ewart; Cuppen, Edwin; Buttner, Reinhard; Caldas, Carlos; Grimmond, Sean; Mullighan, Charles G.; Elemento, Olivier; Rosenquist, Richard; et al.
Abstract: Interrogating the tumor genome in its entirety by whole-genome sequencing (WGS) offers an unprecedented insight into the biology and pathogenesis of cancer, with potential impact on diagnostics, prognostication and therapy selection. WGS is able to detect sequence as well as structural variants and thereby combines central domains of cytogenetics and molecular genetics. Given the potential of WGS in directing targeted therapeutics and clinical decision-making, we envision a gradual transition of the method from research to clinical routine. This review is one out of three within this issue aimed at facilitating this effort, by discussing in-depth analytical validation, clinical interpretation and clinical utility of WGS. The review highlights the requirements for implementing, validating and maintaining a clinical WGS pipeline to obtain high-quality patient-specific data in accordance with the local regulatory landscape. Every step of the WGS pipeline, which includes DNA extraction, library preparation, sequencing, bioinformatics analysis, and data storage, is considered with respect to its logistics, necessities, potential pitfalls, and the required quality management. WGS is likely to drive clinical diagnostics and patient care forward, if requirements and challenges of the technique are recognized and met.